The North Kalimantan Aisyiyah’s Contribution to Empowering Women for the Fulfilment of Political Rights - Eugenia Dhea Adeline; Suryaningsi Suryaningsi; Mohammad Bashar (Salasika, 2022)
The purpose of this study was to determine the ability of the Regional Leader of North Kalimantan Aisyiyah in contributing to the fulfillment of political rights through women's empowerment. The research employed a descriptive qualitative method with a narrative approach. This study focuses on the contribution of North Kalimantan Aisyiyah Regional Leaders in Empowering women to fulfill their political rights. Data analysis involved data collection, reduction, presentation, and conclusion. The results of the study indicatedthat the contribution of the Regional Leader of North Kalimantan Aisyiyah led to effective and responsive steps towards women's empowerment. Aisyiyah, a large organization, offers various programs of social activities including the involvement of women in politics, among them are political education activities. Although 'Aisyiyah is not a political party, it strongly supports its members who want to enter politics. The supporting factor is that government policies are not gender-biased. The women's empowerment programs to fulfill their political rights were good, but the public response to political awareness was low. It was a challenge to deal with.